Selectivity and timing: evidence from the performance of Malaysian unit trusts - Md Nassir, Annuar; Ramadilli Mohd, Shamsher Mohamad; Ngu, Mee Hua (Universiti Putra Malaysia Press, 1997)
This paper presents an empirical examination of the selectivity and timing performance of 31 unit trusts in Malaysia. The empirical results indicate that during the] 990-1 995 period, Malaysian unit trusts appear to possess no market timing ability, except for the Kuala Lumpur Growth Fund. However, there is some evidence of superior selection ability on the part of fund managers in picking up "good" stocks. Eighty-one per cent of the sample of unit trusts are able to beat the market return and the Kuala Lumpur Growth Fund ranked highest in terms of selectivity measure. The study found a positive correlation coefficient of 0.53 between selectivity and timing performance among the unit trusts. Further evidence suggests that 81% of the unit trusts have not achieved the expected level of diversification, and risk-return characteristics of the trusts are generally inconsistent with their stated objectives.